Pengaruh Keamanan, Opini Orang Tua, Fasilitas dan Motivasi Siswa Melalui Kinerja Guru terhadap Keputusan Siswa Bersekolah di Yayasan Pembangunan Ar-Ridho Kota Depok - Agus Sugiyanto; Muhammad Zilal Hamzah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
The purpose of the authors conducting this research is to determine whether there is an influence of the independent variable (X1-X4) on the dependent variable (Y2) and whether or not the influence of the intervening variable (Y1) on the dependent variable (Y2). The type of data in this study, is quantitative data obtained through the results of a survey of students. The study uses primary data that is data obtained directly from the respondents who filled out and developed the questionnaire. Test the validity and reliability using SPSS 24.0. The statistical method used to test the hypothesis in this study uses the multivariate Structural Equation Modeling (SEM) technique with the software used is AMOS 18. The selection of SEM analysis techniques is based on the consideration that SEM has the ability to test structural models simultaneously and efficiently when compared with multivariate techniques another. Hypothesis testing results that have a significant effect as follows: 1. Security has no significant effect on teacher performance. 2. Parents' opinions have a significant effect on teacher performance. 3. School facilities do not significantly influence teacher performance. 4. Motivation has a significant effect on teacher performance. 5. Security does not significantly influence student decisions 6. Opinion has a significant effect on student decisions. 7. School facilities significantly influence student decisions. 8. Motivation has a significant effect on student decisions. 9. Performance has no significant effect on student decisions Keywords: Safety (X1), Parents Opinion (X2), Facilities (X3), Student Motivation (X4), Teacher Performance (Y1), Student Decisions (Y2)